2021
DOI: 10.3390/s21144940
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Robotic Gait Training in Persons with Multiple Sclerosis: A Satisfaction Study

Abstract: Wearable exoskeletons have showed improvements in levels of disability and quality of life in people with neurological disorders. However, it is important to understand users’ perspectives. The aim of this study was to explore the patients’ and physiotherapists’ satisfaction from gait training with the EKSO GT® exoskeleton in people with multiple sclerosis (MS). A cross-sectional study with 54 participants was conducted. Clinical data and self-administered scales data were registered from all patients who perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The average satisfaction score obtained for the ABLE Exoskeleton (31.6 ± 5.7) in study participants was comparable to the EksoGT™ exoskeleton (31.3 ± 5.70) [ 26 ] and the ReWalk device (29.4 ± 2.5) [ 32 ] when tested in individuals with multiple sclerosis, and considerably better than the Marsi Active Knee device (22.4 ± 3.2) when used by individuals with stroke and multiple sclerosis [ 27 ]. In respect to weight (Median: 4.0/Mean: 4.0 ± 1.0), easiness to use (Median: 4.0/Mean: 3.8 ± 0.9) and safety (Median: 4.5, Mean 4.4 ± 0.8) the ABLE Exoskeleton was also better in comparison to the Marsi Active Knee device (Weight: Median 2.8; Easiness to use: Median 2.6; Safety: Median 3.6) and comparable to the EksoGT™ device (Weight: Mean 3.8 ± 1.0; Easiness to use: Mean 3.7 ± 0.9; Safety: Mean 4.3 ± 0.9) [ 26 , 27 ]. These results show that participants are satisfied with the ABLE Exoskeleton and its usability.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The average satisfaction score obtained for the ABLE Exoskeleton (31.6 ± 5.7) in study participants was comparable to the EksoGT™ exoskeleton (31.3 ± 5.70) [ 26 ] and the ReWalk device (29.4 ± 2.5) [ 32 ] when tested in individuals with multiple sclerosis, and considerably better than the Marsi Active Knee device (22.4 ± 3.2) when used by individuals with stroke and multiple sclerosis [ 27 ]. In respect to weight (Median: 4.0/Mean: 4.0 ± 1.0), easiness to use (Median: 4.0/Mean: 3.8 ± 0.9) and safety (Median: 4.5, Mean 4.4 ± 0.8) the ABLE Exoskeleton was also better in comparison to the Marsi Active Knee device (Weight: Median 2.8; Easiness to use: Median 2.6; Safety: Median 3.6) and comparable to the EksoGT™ device (Weight: Mean 3.8 ± 1.0; Easiness to use: Mean 3.7 ± 0.9; Safety: Mean 4.3 ± 0.9) [ 26 , 27 ]. These results show that participants are satisfied with the ABLE Exoskeleton and its usability.…”
Section: Discussionmentioning
confidence: 91%
“…Two additional questionnaires were therefore included, the Quebec User Evaluation of Satisfaction with assistive Technology (QUEST 2.0) and the Psychosocial Impact of Assistive Devices Scale (PIADS). The QUEST 2.0 measures the satisfaction with an assistive device and has been used in previous studies with exoskeletons [ 13 , 26 , 27 ]. The PIADS assesses the psychosocial impact of a device on a sum scale from -78 (negative impact) to + 78 (positive impact) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness, safety and impact on the patient's gait were highly rated, while comfort, weight, and ease of use of the device were reported as elements that should be improved. 9,10 It is known that for a first training with an exoskeleton donning times of 20 min are needed, and for the subsequent trainings 10 to 15 min. Bearing in mind that a normal physiotherapy session is between 30 min and 1 hr, this means that a significant amount of time is lost on the patient setup only.…”
mentioning
confidence: 99%
“…No other study reports user satisfaction for SCI participants or therapists for a comparable robotic exoskeleton with a standard questionnaire such as QUEST 2.0, though studies with multiple sclerosis participants reported lower scores for the EksoGT (31.3 ± 5.70) [25] and the ReWalk (29.4 ± 2.5) [26]. User satisfaction is an extremely important factor for device adoption into standard of care, so future work should focus on more standardized reporting of these metrics.…”
Section: User Satisfactionmentioning
confidence: 99%